Pengalaman Psikologis Pasien Covid-19: Literatur Review: Literatur Review - Carsita, Wenny Nugrahati; Windiramadhan, Alvian Pristy (Viva Medika, 2021)
The Covid-19 disease causes global health problems. The increasing number of cases and deaths causes infected patients to experience not only physical suffering but also psychological problems. Patients infected with Covid-19 report anxiety, depression and post-traumatic stress. Patients with psychological problems will have difficulty controlling the symptoms of the disease, which will prevent recovery. This study aims to determine the psychological experience of Covid-19 patients. The research method used literature review. The data search was sourced from Google scholar, Pubmed, Science direct, and ProQuest using the keyword "psychological experience" "COVID-19 patients" "infection". Inclusion criteria: qualitative study, full text, English, 2020 limited search. The search found 159 articles and resulted in 5 articles that qualify for analysis. The results showed that Covid-19 patients experienced psychological problems at the beginning of diagnosis, during treatment, and after testing negative for Covid-19. Patients infected with Covid-19 are prone to experiencing psychological problems, so that health workers in carrying out treatment are expected to not only focus on physical problems, but also provide treatment related to psychological problems they are experiencing.